Dialogue - Boatright, John R. (Academy of Management Review, 2007)
This article examines the criticism of integrative social contracts theory that it fails to generate a significant number of specific moral norms. Supporters of the theory argue that contracting has an internal morality which includes a number of substantive moral norms. One of these substantive norms is the fiduciary duty that managers have towards shareholders. The author argues that such an internal morality of contracting, if it exists, does not include the moral norms identified by its supporters and it doesn't serve as a basis for any moral norms. Also, the fiduciary duty cannot be derived as part of an internal morality of contracting.